Past, Present, and Future Possibilities for Philosophy and History of Education Finding Space and Time for Research (Springer International Publishing, 2018)
On the occasion of the retirement of Paul Smeyers, this book considers the state and status of the state of the philosophy and history of education today. Over the last 20 years, the conditions in which research takes place have changed considerably. They have done so in ways that are often less than favourable to disciplines such as history and philosophy of education, and the space and time for the practices that constitute these disciplines - of reading, of writing, of collegiality - is increasingly under pressure. During this time, the Research Community on the History and Philosophy of Educational Research has convened annually to bring its critical lenses to bear on these emergent conditions and to suggest ways that educational research might, or ought to, be done otherwise. As co-founder and co-convenor of the Research Community, this volume explores and recounts Paul Smeyers' development of Wittgensteinian scholarship and its legacy in education, his formative role in the development of philosophy of education as an international field, his many international collaborations, the "useless" educational-philosophical deepening of concepts, and the wider educational-philosophical import of this. This gives rise to consideration of the failure of these fields to halt the changes in the governance and status of the university that threatens them, and those practices that remain and that are emerging in academia that we wish to protect, to pass on to the next generation of researchers in these fields. .